1987
DOI: 10.1099/0022-1317-68-2-433
|View full text |Cite
|
Sign up to set email alerts
|

Purified Influenza Virus Nucleoprotein Protects Mice from Lethal Infection

Abstract: SUMMARYLocal administration of nucleoprotein purified from X31 (H3N2) influenza A virus primed for A virus cross-reactive cytotoxic T cells and resulted in substantial protection (75 ~) of mice from a lethal challenge with the heterologous mouse-adapted A/PR/8/34 (H1N1) virus. By following the course of a lethal virus challenge we found that nucleoprotein priming did not prevent virus infection but rather aided recovery. Nucleoprotein-primed mice suffered initial symptoms of infection, i.e. weight loss and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(79 citation statements)
references
References 29 publications
0
78
1
Order By: Relevance
“…In addition, there is substantial evidence for an exogenous or cross-priming pathway in which exogenous Ags that are not expected to gain access to the cytoplasm of an APC are in some manner presented on MHC class I molecules (8 -12). In special situations, CTLs can be induced in vivo by soluble or particulate Ags (13)(14)(15)(16). The relative contribution of each of these pathways to the induction of CD8 ϩ CTLs is an important issue.…”
mentioning
confidence: 99%
“…In addition, there is substantial evidence for an exogenous or cross-priming pathway in which exogenous Ags that are not expected to gain access to the cytoplasm of an APC are in some manner presented on MHC class I molecules (8 -12). In special situations, CTLs can be induced in vivo by soluble or particulate Ags (13)(14)(15)(16). The relative contribution of each of these pathways to the induction of CD8 ϩ CTLs is an important issue.…”
mentioning
confidence: 99%
“…5 In 1987, Wraith D C et al showed that immunization of mice intraperitoneal with NP purified from influenza virus X31 (H3N2) cultured in chick embryo cells would induce cross-reactive cytotoxic T cells, and this CTL reaction could protect 75% of mice against the lethal challenge of heterosubtypic influenza virus A/PR/8/34 (H1N1). 14 In this study, the NP vaccine with C48/80 adjuvant was able to provide the effectively protection for mice, which could resist to the lethal homologous and heterosubtypic influenza virus challenge. It is speculated that the immunization with NP protein in combination with C48/80 adjuvant can strengthen the CTLmediated immune response, so as to clear the influenza virus infection, and that the type of cell-mediated immunity induced Mice were immunized intranasally with various doses of NP vaccine alone or in combination with C48/80.…”
Section: Discussionmentioning
confidence: 99%
“…161 In rodent models, such T cell-based vaccines can protect from challenge. [155][156][157]159,162 In the more rigorous ferret model, they perform less well. 158 The recurrent nature of influenza infection, despite the presence of such conserved antigens in every circulating influenza virus strain, is an indication that immunity directed against these antigens is incomplete, although cell mediated responses appear to contribute to the clearance of infection in humans.…”
Section: Universal Influenza Vaccine Approachesmentioning
confidence: 99%
“…[155][156][157][158][159][160] Vaccines based solely on conserved internal antigens must rely on cell-mediated immunity, because the target antigens are not exposed on the surface of an influenza virion for antibody binding. 161 In rodent models, such T cell-based vaccines can protect from challenge.…”
Section: Universal Influenza Vaccine Approachesmentioning
confidence: 99%